INTENSIFIKASI PEMUNGUTAN PAJAK MELALUI PERBAIKAN PELAYANAN (Kasus PBB dan BPHTB di Kantor Pelayanan Malang) - Munawar Ismail (Journal of Indonesian Economy and Business (JIEB), 2005)
Tax collection intensification through service quality improvement is an efficient way toincrease the role of tax as a main source of government revenue. The objective of this study is to evaluate the service quality of Malang Property-Tax Office delivered to taxpayers in the view of their own perception. The study found that the taxpayers expectation of the service dimensions that consists of tangibles, assurance and accessibility had been met so it has to be continued. Yet, while the taxpayers expectation of the service dimensions that contains reliability and responsiveness was not fullfiled. Therefore, in the future, Malang Property-Tax Office should make more attention on it. Other finding is that there was no dimension of the services that the taxpayers consider it worse.Keywords: property tax, intensification, service quality